Psychometric properties of a clinical assessment tool in the postgraduate midwifery programme, Botswana - Itumeleng Rasetshwane; Nombulelo V. Sepeng; Ramadimetja S. Mooa (AOSIS, 2023)
Background: The psychometric properties of a clinical assessment tool used in the postgraduate midwifery programme in Botswana have not been evaluated. A lack of reliable and valid clinical assessment tools contributes to inconsistencies in clinical assessment in midwifery programmes. Objectives: This study aimed to evaluate the internal consistency and content validity of a clinical assessment tool used in the postgraduate midwifery programme in Botswana. Method: For internal consistency, we calculated the total-item correlation and Cronbach's alpha coefficient. For content validity, subject matter experts completed a checklist to evaluate the relevance and clarity of each competency in the clinical assessment tool. The checklist included questions with Likert-scale responses, indicating the level of agreement. Results: The clinical assessment tool had a good reliability, with a Cronbach's alpha of 0.837. The corrected item total correlation values ranged from -0.043 to 0.880 and the Cronbach's alpha (if item deleted) ranged from 0.079 to 0.865. Overall content validity ratio was 0.95, and content validity index was 0.97. Item content validity indices ranged from 0.8 to 1.0. The overall scale content validity index was 0.97 and the scale content validity index using universal agreement was 0.75. Conclusion: The clinical assessment tool used in the postgraduate midwifery programme in Botswana has acceptable reliability. Most of the competencies included in the clinical assessment tool were relevant and clear. Certain competencies need to be reviewed to improve the reliability and validity of the clinical assessment tool. Contribution: The clinical assessment tool currently used in the postgraduate midwifery programme in Botswana had acceptable internal consistency reliability and validity.